Band Structure Effects on the Charge Exchange Processes in H+ Colliding with a Cu(111) Surface - Quintero Riascos, Vanessa Alexandra (2018)
The low-energy ion scattering (LEIS) technique was used to experimentally determine the formation of positive and negative ions in the scattering of protons by a Cu(111) surface for a large scattering angle in the backscattering configuration and a wide range of incoming energies (2-8 keV). Two different collisional geometries were analyzed for a 135° fixed scattering angle: 45°/90° and 67.5°/67.5° incoming/exit angles measured with respect to the target surface. The total fraction of backscattered ions ranges from 10% to 25%, and a peculiarly high yield of negative ions, which always exceeds that of positive ions, was detected for the whole energy range analyzed. A strong dependence of the measured ion fractions with the geometrical conditions was experimentally found. On the theoretical side, a first-principles quantum-mechanical formalism that takes into account the three possible final charge states of the H+ in a correlated way and the fine details of the band structure of the Cu(111) surface was applied to describe the charge transfer processes involved in the experimental situation. The theoretical calculation leads to a nonmonotonous dependence with the incoming energy that properly describes the experimental results, especially the negative ion fraction in the specular collisional geometry. The oscillatory behavior predicted by the theory in the range of low energies is clear evidence of the charge exchange between localized states, that is, the situation related with the presence of the surface state immersed in the L-gap present in the Cu(111) surface. The positive ion fraction is discussed for the first time for this collisional system. The differences found between the measurements and the theory seem to indicate that the neutralization to excited states and also the formation of excited negative hydrogen ions are possible charge exchange channels in the dynamic process analyzed.